Strengthening basic soccer skills through a ball-handling training program for young children at SSB Rabbani Putra Mandiri - Alfiansyah, Ferdy Nur; Hariadi, Imam (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2025)
Dribbling ability is an essential basic skill in early childhood soccer. However, preliminary observations at SSB Rabbani Putra Mandiri show that the 10-year-old age group still has difficulties maintaining ball control while dribbling, such as the ball being too far from the feet, uncontrolled direction of movement, and being easily captured by opponents. This service activity aims to improve dribbling skills through a specially designed ball feeling training program based on the principles of Long-Term Athlete Development (LTAD). The implementation method used an experimental one-group pretest-posttest design with 20 participants. The training program was conducted for 22 meetings, and dribbling skills were measured using tests from Winarno (2006). The evaluation results showed a significant increase in the average value of dribbling skills, from 51.35 in the pretest to 61.75 in the posttest. The Paired T-Test test results showed a p value <0.05, which means there is a significant difference between before and after training. In conclusion, the ball feeling training program effectively improves dribbling skills in early age players. This program is expected to be adopted as part of the early childhood football training curriculum on an ongoing basis. This service activity supports the achievement of the SDGs, especially Goal 3 (healthy and prosperous life) and Goal 4 (quality education), through providing quality education.